Efektivitas Syzygium Polyanthum sebagai Inhibitor Korosi AISI 1037 pada Media Air Gambut - Masnur, Dedy; Fatra, Warman; Nawangsari, Putri; Hadi, Syafwan (Fakultas Teknik UMRI, 2026)
Corrosion of carbon steel in peat water environments is a critical issue due to the acidic nature and high content of organic acids in the medium. This study investigates the corrosion rate and inhibition efficiency of Syzygium polyanthum (bay leaf) extract as a natural corrosion inhibitor for AISI 1037 carbon steel in peat water. The extract was prepared using a maceration method followed by solvent removal with a rotary evaporator. Steel specimens were immersed in peat water without inhibitor and with inhibitor mass concentrations of 3%, 6%, and 9% (v/v) for 28 days. Corrosion rates were determined using the weight loss method, supported by visual surface analysis. The results indicate that bay leaf extract significantly reduces the corrosion rate of AISI 1037 steel. The highest inhibition efficiency of 38.83% was achieved at a concentration of 9% v/v, corresponding to a corrosion rate of 1.66 mpy. These findings demonstrate the potential of bay leaf extract as an environmentally friendly corrosion inhibitor for carbon steel in peat water environments.